ELASTICITY OF PYROPE AND MAJORITE-PYROPE SOLID SOLUTIONS TO HIGH TEMPERATURES - Sinogeikin S.V.; Bass J.D. (My University, 2002)
Majorite-garnet solid solutions are major mineral phases in the Earth's upper mantle and transition zone. Here we present the first Brillouin scattering measurements of the elasticity of majorite (Mj, Mg4Si4O12)-pyrope (Py, Mg3Al2Si3O12) solid solutions (Mj50Py50 and Mj80Py20) and single-crystal elasticity of pure synthetic pyrope at temperatures up to 800°C. The temperature derivatives of the adiabatic bulk (KS) and shear (μ) moduli for all compositions along the Mj-Py join are the same within the experimental uncertainties (-#KS/#T=14.0-14.5(20) MPa/K, -#μ/#T=8.3-9.2(10) MPa/K). The temperature dependence of the acoustic velocities for Mj-Py solid solutions is about half that of other major transition zone minerals. This implies that temperature variations in the transition zone, inferred from lateral velocity heterogeneity, can be significantly underestimated if the properties of majoritic garnet are not taken into account.
Keywords: MAJORITE; PYROPE; CRYSTAL STRUCTURE; ELASTICITY; TEMPERATURE; ELASTIC PROPERTIES; TRANSITION ZONES